Dual-functional peptide with defective interfering genes effectively protects mice against avian and seasonal influenza - Hanjun Zhao (Nature Portfolio, 2018)
A limited number of therapeutics is available to treat influenza A virus (IAV) infections. Here, the authors show that defective interfering genes, delivered with a dual-functional peptide that enables intracellular accumulation and prevents endosomal acidification, inhibit IAV replication in vitro and in vivo.